Do Healing Rates Differ Between Medication-Related and Medication-Unrelated Osteonecrosis of the Jaw? - Fujimori, Masaki; Toriyabe, Yoshiyuki; Sakakibara, Noriyuki; Nojima, Masanori; Makino, Shujiroh; Shimazaki, Kosuke; Miyasawa, Masayoshi; Miyate, Hiroki; Kitada, Hideaki; Satoh, Yuji; Yamashita, Tetsuro; Nakajima, Yoritoshi; et al. (Journal of oral and maxillofacial surgery, 2025)
The healing rates, time to complete healing, effectiveness of operative therapy, and factors associated with healing for medication-related osteonecrosis of the jaw (MRONJ) and medication-unrelated osteonecrosis of the jaw (MUONJ) remain unclear. The study aimed to estimate and compare the healing rates between patients with MRONJ and MUONJ and identify prognostic factors associated with healing. A 25-center prospective cohort study was performed—the investigators enrolled patients with ONJ treated using a standardized therapeutic protocol between 2013 and 2016. Patients with a history of radiation therapy to the jaws were excluded. The primary predictor variable was the ONJ diagnosis. The secondary predictors involved a set of heterogenous variables grouped into demographic, medical, clinical condition, and perioperative categories. The primary outcome variable was treatment duration, defined as the time (in months) between therapy initiation and site healing, date of the final visit, or loss to follow-up. Not applicable. Descriptive statistics and cumulative healing rates were calculated. P < .05 was considered significant. The sample comprised 332 subjects with a mean age of 72.3 ± 11.1 years, among whom 116 (34.9%) were male. The MUONJ and MRONJ groups included 41 (12.3%) and 291 (87.7%) subjects, respectively, exhibiting 1-year cumulative healing rates of 92.1 and 47.3% (P < .01), respectively. The hazard ratio for complete healing was 3.7 (95% CI = 2.5 to 5.3, P < .01) in subjects with MUONJ compared with those with MRONJ. The median time to complete healing was 6 (3.8 to 8.2) months in the MUONJ group, while less than half of the subjects in the MRONJ group healed within 12 months. The 1-year cumulative healing rate was 92.1 and 47.3% (P < .01) in the operative therapy and nonoperative therapy groups, respectively. MUONJ was associated with better healing rates and a shorter time to healing compared with MRONJ. Operative therapy also showed potential benefits. Decisions for treating ONJ should be based on these findings alongside individual patient needs and conditions.